Football Psychology - From Theory to Practice (Routledge, 2019)
Presenting an empirically underpinned synthesis of research and theory, while offering guidance for applied practitioners, this is the first book to comprehensively map the psychology of learning, playing, and coaching the world`s favourite sport. The book provides a complete analysis of key topics that capture the broad range of football psychology such as personality, motivation, cognition, and emotion; coaching and team essentials; psychological skills for performance enhancement; and developing players in youth football. Including contributions from a range of international researchers, each chapter provides a review of the relevant literature, key theories, real-world examples, and reflections on how knowledge can be applied in practice. Split into four sections, the book covers a diverse range of topics relevant not only to coaching and performance but also to personality development and health promotion. Essential reading for any student, researcher, or professional in the area, the book is the most cutting-edge overview of how psychology can explain and improve the way football is both played and understood.